2010
DOI: 10.1111/j.1442-2050.2009.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflux esophagitis and columnar-lined esophagus after cervical esophagogastrostomy (following esophagectomy)

Abstract: Reflux esophagitis (RE) and columnar-lined esophagus (CLE) are frequently observed after esophagectomy. The incidence of these conditions according to time and to the route of esophageal reconstruction after esophagectomy remains unknown. The aim of this study was to clarify any changes and differences of the incidence of RE and CLE in patients who underwent gastric tube reconstruction after esophagectomy. A hundred patients who underwent cervical esophagogastrostomy after resection of the thoracic esophagus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…RE is often seen in patients who have undergone esophagogastrostomy after esophagectomy, and affects the quality of life in those patients 3,4,7,8,13,14 . The incidence of RE after esophagectomy was reported as 71.6% by Shibuya et al ., 3 as 58.3% by Yamamoto et al ., 4 as 32.1% by Kim et al ., 13 and as 45.9–70.0% by da Rocha et al 14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…RE is often seen in patients who have undergone esophagogastrostomy after esophagectomy, and affects the quality of life in those patients 3,4,7,8,13,14 . The incidence of RE after esophagectomy was reported as 71.6% by Shibuya et al ., 3 as 58.3% by Yamamoto et al ., 4 as 32.1% by Kim et al ., 13 and as 45.9–70.0% by da Rocha et al 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several reports have shown a correlation between acid and/or bile reflux, and RE or Barrett's esophagus after esophagectomy 3–7 . We have previously reported that 42% of patients developed RE at 1 month after esophagectomy 8 . However, the influence of acid and/or bile reflux and other clinical factors on RE is still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…A Japanese study published in 2010 predominantly considered reflux esophagitis in the esophageal remnant, but some data on columnar metaplasia is included . Data were available for 100 patients at 1 year, and a 14% prevalence of metaplasia is quoted.…”
Section: Prevalence Of Post‐esophagectomy Barrett's In the Adult Surgmentioning
confidence: 99%
“…Four studies evaluated the association between time from surgery and the presence of Barrett's‐like metaplasia . Nishimura and colleagues, in their study of 100 patients, describe no cases of columnar metaplasia at 1 month, 14% prevalence at 1 year, and 40% prevalence in a subgroup of 58 patients who were followed up for 2 years . The other study which reports a significant association between the time from surgery and the presence of columnar metaplasia is that of da Rocha and colleagues .…”
Section: Timescale For the Development Of Post‐esophagectomy Barrett'smentioning
confidence: 99%
See 1 more Smart Citation